A Comprehensive Approach to the Beer Tourism Phenomenon. - Sánchez-Cubo, Francisco; Benavides-Chicón, Carlos Guillermo; Sánchez-Ollero, José Luis (Emerald, 2025)
Purpose: Beer is the most consumed alcoholic beverage worldwide, and beverages play a crucial role in dining. During the last few years, beer tourism has become an attractive tourism segment. However, despite the growing body of literature on craft beer, the relationships within the tourism sphere still need to be explored from a broader perspective. Study design/methodology/approach: Using data from a self-administered survey, quantitative methods were applied to shed light on such relationships. Specifically, a PLS-SEM model was proposed, and between-group differences tests were carried out, including U Mann-Whitney and multigroup analyses (PLS-MGA). Findings: The above methods demonstrated the existence of a contextual construct (“Context”) that helps explain the personal behaviours towards beer (“Personal”) before further analysing the beer and tourism relationships. Moreover, the effects of such personal behaviour on the preparation of the trip (“PreTrip”) and the attitudes after the trip (“PostTrip”) were also corroborated. Plus, partial differences between groups were found regarding the preferred type of beer and the origin of the tourists, while sex and frequency of consumption retrieved non-significant results. Originality/value: This work stands out as the first one to comprehensively address the latent relationships between beer and tourism, and one of the first to include general beer consumers in the sample, not limiting it to craft beer consumers.
Versión aceptada para publicación.
https://openpolicyfinder.jisc.ac.uk/id/publication/1289?from=single_hit
Keywords: Turismo; Cerveza; Consumidores - Conducta; Beer; Beer tourism; PLS-SEM; Tourism; Tourist behaviour